Preoperative Carotid Duplex Scanning in Patients Undergoing Coronary Artery Bypass Grafting - Hakan Kara (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: The aim of this study was to determine the prevalence and risk factors of carotid artery stenosis (CAS) using carotid duplex ultrasound in patients undergoing coronary artery bypass grafting (CABG). Methods: This retrospective study was conducted between January 2017 and January 2018 and included 166 consecutive patients [130 males (78.31%), 36 females (21.69%); mean age: 64.25±9.78 years] who underwent elective and isolated CABG. Patients who had significant CAS (≥50% stenosis) were compared with patients who had non-significant CAS (<50% stenosis). Logistic regression analysis was applied across the selected parameters to identify risk factors for significant CAS. Results: Of all patients, 36 (21.68%) had CAS ≥50% and 8 (4.81%) had unilateral carotid stenosis ≥70%. Carotid endarterectomy/CABG was performed simultaneously in five (3.01%) patients. None of these patients had cardiac and neurological problems during the postoperative period. The overall incidence of cerebrovascular accident (CVA) after CABG was 1.20% (n=2). Age (P=0.011) and history of CVA (P=0.035) were significantly higher in the CAS ≥50 group than in the CAS <50 group. Significant CAS was identified as a risk factor for postoperative CVA (P=0.013). Conclusion: Age and history of CVA were identified as risk factors for significant CAS. Furthermore, significant CAS was identified as a risk factor for postoperative CVA. For this reason, carotid screening is recommended for patients undergoing CABG even in the absence of associated risk factors.